Democracia e direitos sociais: histórico e implicações para as políticas educacionais brasileiras - Doracy Dias Aguiar de Carvalho; Roberto Francisco de Carvalho (Revista Katálysis)
This article discusses democracy within the scope of the capitalist society, using theoretical and documentary research. The study sought to build concepts around the limits of substantive, socialist, and representative liberal democracy. It shows some implications of liberal democracy for Brazilian social rights and public policies that have been dismantled by neoliberal counter-reforms, such as the policies on education. The study also exposes the need to protect national-popular education, capable of contributing to the construction of substantive democracy and new sociability, which implies in relations of equality and coordination between politics and economy from the perspective of human emancipation.